Paciente masculino de 64 años de edad con enfermedad pulmonar obstructiva crónica. - Monar Chica Luis Estefano (2020)
The present clinical case is a 64-year-old male patient who reports a clinical picture that began approximately 3 months ago characterized by a productive cough of moderate intensity, mucous appearance (whitish) plus mild pain in the chest that increases with coughing, reports that at night he feels that he wheezes when breathing and has discomfort in the throat in the morning that is alleviated with the expulsion of phlegm, he refers to mild fatigue and tiredness but that increases in intensity when performing activities of effort. that causes respiratory distress and dyspnea on maximal exertion, reports that food consumption has decreased and has noticed weight loss, the doctor performs a spirometry examination resulting in an obstructive pattern FVC> 96% FEV1 / FVC <62 decreased by which it is diagnosed with chronic obstructive pulmonary disease. Nutritional status is assessed with anthropometric parameters, presenting a severe weight loss percentage of 8.5% in 3 months, body mass index of 18.5kg / m2 and a cut-off point of the triceps fold with risk of malnutrition, in the Biochemical evaluation presents leukocytosis and its ingestion through the 24-hour recall presented a hypocaloric and hypoproteic diet, then through nutritional intervention with the aim of maintaining a nutritional state and avoiding complications, a hypercaloric hyperproteic diet with carbohydrate control is prescribed divided into 5 meal times, where it is evident that through the established plan a favorable response is observed when obtaining a weight gain and a stable state of the patient.